EVALUASI KEBIJAKAN PROGRAM KELUARGA HARAPAN DI KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Huzaipa, Huzaipa (Katalogis, 2014)
The research aims to evaluate the policy of Hope Family Program Sigi Biromaru Sub districtof Sigi Regency. The research employed qualitative approach. The research question was how the evaluation of Hope Family Program Sigi Biromaru Sub district. The informants were determined through snowball technique by selecting 11 persons who considered know and understand the problem examined. The techniques of data analysis were editing, categorization, giving meaning and drawing conclusion.  The theory used was about Policy Evaluation Criteria from William N. Dunn  covering  aspects  of  effectiveness,  efficiency,  adequacy,  equality,  responsiveness,  and accuracy.  The  research  revealed  that  the  evaluation  of  hope  family  program  policy  in  Sigi Biromaru Sub district that using evaluation criteria of the theory applied had not been successful in obtaining the goal. The increasing of children activity of hope family program in education aspect, increasing nutrition status of the pregnant women in healthy aspect, parturition and children under five  years,  and  the  decreasing  of  poverty  rate  from  531  of  very  poor  households  up  to  497 households or it was 0.93%, however, the policy of hope family program could not be able to increase the economy condition of very poor households   because the respondents were still in troubled and hopeless position. The factors influencing the policy program in Sigi Biromaru Sub districts were the role of accompany and operator of Hope Family Program, coordination between related institution and budget support.